Gaya Hidup Berbelanja dan Keterlibatan Konsumen Yang Mempengaruhi Pembelian Impulsif Produk Fashion di Summarecon Mall Bekasi - Wirda Nursanti; Andina Hafizah; Ali Mutaufiq; Edy Supryantony (Fakultas Ekonomi Universitas Borobudur, 2023)
This research aims to investigate the influence of shopping lifestyle and consumer involvement ent on impulse buyingof fashion products at shopping store Summarecon Mall Bekasi. Data were collected through surveys administred to mall visitors who were potential candidates for impulse purchases of fashion products. The sample consisted of 384 respondents randomly selected. The result of data analysis using multiple regression methods how that shopping lifestyle has significant impact on impulse buying of fashion products. This indicates that shopping lifestyle , such as tendency to follow the latest fashion trends, affects the decision to make impulse purchases of fashion products at shopping store Summarecon Mall Bekasi. Further more, consumer involvement wa also found to have significant positive influence on impulse buying of fashion products. Consumers who feel emotionally or cognitivel engaged with fashion products are more likely to engage in impulse buying. The findings of this study provide valuable insights for the management of Summarecon Mall Bekasi and fashion brands operating within it. Understanding shopping lifestyle and the level of consumer involvement can help in designing more effective marketing strategis to stimulate impulse buying of fashion products. In an ever-changing fshion landscape, an emphasis on trends and consumer involvement can be pivotal in maintaining the appeal and growth of fashion products businesses.